2018
DOI: 10.1128/iai.00810-17
|View full text |Cite
|
Sign up to set email alerts
|

Thioester-Containing Proteins 2 and 4 Affect the Metabolic Activity and Inflammation Response in Drosophila

Abstract: is an outstanding model for studying host antipathogen defense. Although substantial progress has been made in understanding how metabolism and immunity are interrelated in flies, little information has been obtained on the molecular players that regulate metabolism and inflammation in during pathogenic infection. Recently, we reported that the inactivation of thioester-containing protein 2 () and promotes survival and decreases the bacterial burden in flies upon infection with the virulent pathogens and Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
(105 reference statements)
1
15
0
Order By: Relevance
“…Moreover, it was recently evidenced that some invertebrate TEPs also play roles in other functions than immunity. Drosophila MCR was found to be implicated in development [73], nitric oxide regulation, and metabolic processes [74,75], while AgTEP1 was shown to increase male fertility [76].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently evidenced that some invertebrate TEPs also play roles in other functions than immunity. Drosophila MCR was found to be implicated in development [73], nitric oxide regulation, and metabolic processes [74,75], while AgTEP1 was shown to increase male fertility [76].…”
Section: Discussionmentioning
confidence: 99%
“…In the fat body, the Jak-Stat pathway has mainly been shown to induce the expression of cytokines (103) and of a putative opsonin belonging to the TEP family (104). Remarkably, several Tep genes have been shown to participate in antibacterial immunity after NBC infestation in D. melanogaster (91, 105107). All of these down-regulations could thus impair the insect’s immune response to the NBC.…”
Section: Resultsmentioning
confidence: 99%
“…Because certain TEPs in D. melanogaster were shown to play a regulatory role by inducing humoral and cellular immune activities against Photorhabdus pathogens [18,19,22], these molecules also form a reliable indicator for their potential multipurpose involvement in linking host immunity and metabolism in the presence of pathogenic bacteria. Of note, injection of P. luminescens into the hemocoel of background wild-type flies upregulates both Tep2 and Tep4 in the fat body as well as Tep4 in the gut, whereas injection of P. asymbiotica increases the expression of Tep4 in the fat body only (Figure 1) [32]. Although the tissue-specific expression pattern of Tep genes in D. melanogaster varies upon infection with different bacterial pathogens [33], these results demonstrate that certain Tep genes are expressed in the two metabolic tissues of the fly-fat body and gut-in response to Photorhabdus systemic infection.…”
Section: Thioester-containing Proteins and Drosophila Metabolism Durimentioning
confidence: 99%
“…To address these issues, a recent study monitored the metabolic activity in D. melanogaster TEP-deficient flies during response to infection by two Photorhabdus species as well as by a nonpathogenic strain of E. coli used as control and estimated the amounts of different metabolites including carbohydrates and lipids [32]. Results from these experiments first revealed that trehalose levels are drastically affected in flies with compromised Tep2, regardless of whether they are infected with pathogenic Photorhabdus bacteria or nonpathogenic E. coli.…”
Section: Thioester-containing Proteins and Drosophila Metabolism Durimentioning
confidence: 99%
See 1 more Smart Citation